2015
DOI: 10.1016/j.apsb.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids and sphingosine-1-phosphate receptor 2 in hepatic lipid metabolism

Abstract: The liver is the central organ involved in lipid metabolism. Dyslipidemia and its related disorders, including non-alcoholic fatty liver disease (NAFLD), obesity and other metabolic diseases, are of increasing public health concern due to their increasing prevalence in the population. Besides their well-characterized functions in cholesterol homoeostasis and nutrient absorption, bile acids are also important metabolic regulators and function as signaling hormones by activating specific nuclear receptors, G-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 74 publications
2
76
1
Order By: Relevance
“…In addition, TCA induced a rapid downregulation of the gluconeogenesis genes, PEPCK and G6Pase, and a marked upregulation of SHP mRNA in the livers (42). This illustrates that bile acid activation of S1PR2 has insulin-like activity in hepatic glucose regulation (9). Further, it has been reported that hepatic overexpression of SphK2 in mice led to elevated S1P and reduced ceramide, sphingomyelin, and glucosylceramide in plasma and liver, and ameliorated glucose intolerance and insulin resistance by improving hepatic insulin signaling (44).…”
Section: S1pr2 and Bile Duct Cancermentioning
confidence: 78%
See 4 more Smart Citations
“…In addition, TCA induced a rapid downregulation of the gluconeogenesis genes, PEPCK and G6Pase, and a marked upregulation of SHP mRNA in the livers (42). This illustrates that bile acid activation of S1PR2 has insulin-like activity in hepatic glucose regulation (9). Further, it has been reported that hepatic overexpression of SphK2 in mice led to elevated S1P and reduced ceramide, sphingomyelin, and glucosylceramide in plasma and liver, and ameliorated glucose intolerance and insulin resistance by improving hepatic insulin signaling (44).…”
Section: S1pr2 and Bile Duct Cancermentioning
confidence: 78%
“…These data suggest that a bile acid induced an increase in SphK2 through S1PR2 activation. In fact, mice deficient in SphK2 also rapidly developed fatty livers on a high-fat diet, suggesting the importance of S1PR2 and SphK2 in regulating liver lipid metabolism (9,11). In mice fed a high-fat diet, overexpression of SphK2 led to elevated S1P and reduced ceramide, sphingomyelin, and glucosylceramide in plasma and in the liver (44).…”
Section: Conjugated Bile Acids Activate S1pr2mentioning
confidence: 99%
See 3 more Smart Citations